2016
DOI: 10.1371/journal.pone.0168196
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Surface Metabolite Composition of Fucus vesiculosus and Fucus serratus from the Baltic Sea

Abstract: Perennial macroalgae within the genus Fucus are known to exude metabolites through their outer thallus surface. Some of these metabolites have pro- and/or antifouling properties. Seasonal fluctuations of natural fouling pressure and chemical fouling control strength against micro- and macrofoulers have previously been observed in Fucus, suggesting that control strength varies with threat. To date, a study on the seasonal composition of surface associated metabolites, responsible for much of the fouling control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 77 publications
2
34
0
Order By: Relevance
“…; Rickert et al . ), which means that marine macroalgae can adjust their anti‐epibiont activities to quantitative or qualitative changes in colonization pressure. In both regions where we collected algae, diatoms are more abundant from April to June than from August to October (Trimonis, Vaikutiene & Gulbinskas ; Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Rickert et al . ), which means that marine macroalgae can adjust their anti‐epibiont activities to quantitative or qualitative changes in colonization pressure. In both regions where we collected algae, diatoms are more abundant from April to June than from August to October (Trimonis, Vaikutiene & Gulbinskas ; Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…In fact, seaweeds are increasingly being recognized as a rich natural resource of valuable biochemical constituents (including high-quality proteins, bioactive peptides, dietary fiber, polysaccharides, lipids, fatty acids, minerals, vitamins, pigments, and phytochemicals such as polyphenols), that may have protective effects against allergy, cancers, degenerative disorders, diabetes, digestive disorders, heart diseases, hypertension, inflammation, lipidemia, obesity, and oxidative stress [1,2,3,4,5,6]. However, as is well established, the biochemical composition of seaweeds, and consequently their nutritional and medicinal values, depends on many factors, such as: species and its developmental stage, spatial and temporal changes in environmental parameters (including light, temperature, nutrients, and salinity) and biotic interactions [1,6,7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…The fact that propagules of marine fouling organisms settle and attach easily on immersed untreated solid surfaces, while many slimy or gel-like surfaces, such as marine algae (Bhadury & Wright 2004) and sea anemones (Atalah et al 2013) are more resistant to epibiosis, has inspired to explore the potential of hydrogels and other highly hydrophilic materials for the control of marine biofouling (Ekblad et al 2008, Larsson et al 2007, Yandi et al 2014, and for informing the development of useful coatings. The prevention of epibiosis of marine organisms is sometimes the combined result of a strongly hydrated surface and, for example, secretion of substances with antifouling activity by the basibiont (Dobretsov et al 2013, Fusetani 2004, Rickert et al 2015, continuous production of mucus (Wahl et al 1998), or other specifically developed antifouling mechanisms. It has also been found that attachment and settlement of marine organisms on synthetic neutral hydrogels or hydrophilic polymers is very low both in laboratory and in marine field tests (up to 1 h exposure to bacteria or algal spores, 48 h incubation with barnacle cyprids, up to two months field immersion) (Ekblad et al 2008, Xie et al 2011, Yandi et al 2014.…”
Section: Introductionmentioning
confidence: 99%